Formal Foundations of Reuse and Domain Engineering 11th International Conference on Software Reuse, ICSR 2009, Falls Church, VA, USA, September 27-30, 2009. Proceedings - Edwards, Stephen H.; Kulczycki, Gregory. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 11th International Conference on Software Reuse, ICSR 2009, held in Falls Church, VA, USA, in September 2009. The 28 full papers were caryfully selected from numerous submissions. 2009 was the year that ICSR went back to its roots. The theme was Formal Foundations of Reuse and Domain Engineering. The theory and formal foundations that underlie current reuse and domain engineering practice were explored and current advancements to get an idea of where the field of reuse was headed, were looked at. Many of the papers in these proceedings reflect that theme, e.g. component reuse and verification, feature modeling, generators and model-driven development, industry experience, product lines, reuse and patterns, service-oriented environments.